2015
DOI: 10.1039/c4an02282c
|View full text |Cite
|
Sign up to set email alerts
|

Versatile G-quadruplex-mediated strategies in label-free biosensors and logic systems

Abstract: G-quadruplex (G4), as one of the significant functional nucleic acids (FNAs), has attracted researchers' wide attention, and in particular has been employed for the construction of label-free molecular sensors and logic systems based on the peroxidase-like activity of the G4-hemin complex and G4-enhanced luminescence of G4-binding organic dyes. Its cation-dependent conformation and stability provide opportunities for the recognition of metal ion inputs and application of a split G4 strategy. Moreover, coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 160 publications
(263 reference statements)
0
23
0
Order By: Relevance
“…Finally, we highlight recent examples of G-quadruplex small-molecule probes that have been used as G-quadruplex DNA imaging agents in living cells. Here, we focus mainly on examples that have been described in the last few years, as previous reviews on G-quadruplex probes describing earlier developments have been published by our group and others (Neo et al, 2012;Largy et al, 2013;Ren et al, 2015;Ruttkay-Nedecky et al, 2013;Vummidi et al, 2013). For ease of access, a summary of the photophysical properties of the G-quadruplex probes highlighted in this review can be found in Table 1.…”
Section: Introductionmentioning
confidence: 94%
“…Finally, we highlight recent examples of G-quadruplex small-molecule probes that have been used as G-quadruplex DNA imaging agents in living cells. Here, we focus mainly on examples that have been described in the last few years, as previous reviews on G-quadruplex probes describing earlier developments have been published by our group and others (Neo et al, 2012;Largy et al, 2013;Ren et al, 2015;Ruttkay-Nedecky et al, 2013;Vummidi et al, 2013). For ease of access, a summary of the photophysical properties of the G-quadruplex probes highlighted in this review can be found in Table 1.…”
Section: Introductionmentioning
confidence: 94%
“…Incorporating nanoparticles in the assay serves to dramatically increase the surface area on which color precursor molecules may be docked. The AuNP-based G-quadruplex (quadruple-stranded DNA) enhances the luminescence of certain organic dyes in the presence of hemin (86). Based on this finding, Luo et al (72) introduced a AuNP colorimetric assay for the Salmonella invA gene.…”
Section: Detection Methods Based On Nanomaterialsmentioning
confidence: 99%
“…They can catalyze the oxidation of dyes such as 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulphonic acid) (ABTS) in the presence of hemin and hydrogen peroxide, which produces a color change (Figure B). This activity is known as peroxidase activity, and therefore, these types of DNA molecules are also called peroxidase DNAzymes . They can also bind to certain fluorogenic molecules, such as protoporphyrin IX (PPIX), to produce a strong fluorescence signal (Figure C) .…”
Section: Figurementioning
confidence: 99%
“…This activity is known as peroxidase activity,a nd therefore, theset ypes of DNA molecules are also called peroxidaseD NAzymes. [24][25][26] They can also bind to certain fluorogenic molecules, such as protoporphyrin IX (PPIX), to produce as trong fluorescence signal ( Figure 1C). [27][28][29] Therefore, ULX can function as an excellent colorimetric or fluorescent signaling module to build a biosensing system to achieve target detection in 7MU.…”
mentioning
confidence: 99%